Role of orexin/hypocretin in conditioned sucrose-seeking in rats - Cason, Angie M. (2012)
RATIONALE: The orexin/hypocretin system has recently been implicated in reward-seeking, especially for highly salient food and drug rewards. We reasoned that this system may be strongly engaged during periods of reward restriction, including food restriction. OBJECTIVES: This study examined the involvement of the orexin (Orx) system in responding for sucrose, and in cue-induced reinstatement of extinguished sucrose-seeking, in ad libitum fed vs. food-restricted male subjects. METHODS: Sprague Dawley rats (n=108) were trained to self-administer sucrose, and we determined the effects of pretreatment with the OxR1 receptor antagonist SB 334867 (SB; 10–30 mg/kg) on fixed ratio (FR) or progressive ratio (PR) sucrose self-administration, as well as on cue-induced reinstatement of sucrose-seeking. Finally, expression of the immediate early gene c-fos in Orx neurons was examined after self-administration, late extinction or cue-induced reinstatement of sucrose seeking. RESULTS: SB decreased lever responding (by about 1/3) and the number of reinforcers earned during FR, and less so during PR, schedules and decreased cue-induced reinstatement to sucrose-seeking to extinction levels, predominately in food-restricted rats. Additionally, Fos expression in Orx neurons in perifornical and dorsomedial hypothalamus was increased during extinction. CONCLUSIONS: These results indicate that signaling at the OxR1 receptor is involved in pronounced sucrose reinforcement, and reinstatement of sucrose-seeking elicited by sucrose-paired cues, in food-restricted subjects. These findings lead us to conclude that conditioned activation of Orx neurons increases motivation for food reward during food restriction.